Development of Critical Thinking Instrument with Minimum Competency Assessment Characters on Elasticity and Hooke’s Law - Ningsih, Jayanti Eka Sari; Susanti, Dwi; Serevina, Vina; Maulana, Slamet (Jurnal Pendidikan Fisika Indonesia, 2024)
Indonesia government sets a minimum competency assessment to prepare students in Indonesia for the 21st century and one of thinking skill that students must has been critical thinking skills. This study aims to develop an instrument test to measure critical skill that students have which are which followed by the minimum competency assessment for elasticity and Hooke’s Law high secondary level. Furthermore, the instrument was developed on a research and development model and based on the development of an 8 steps test instrument by Mc Entire. The instrument test was validated by material experts who had been analyzed using Aiken V. This instrument tested on senior high school students and categorized as having a high reliability. Based on this, the measurement critical of thinking which is characterized by assessment competency minimum on elasticity and Hooke's law, in general can be done with this instrument. This research is beneficials as character-based essay tests to enhance critical thinking skills in high school students, focusing on elasticity and Hooke's law. It's intended as a tool to develop and refine these essential skills required for minimum competency assessments.